PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR PADA MATA KULIAH SOLFEGIO - Anizaputri, Rizky Sekarini (Program Studi Pendidikan Musik, 2022)
The purpose of this study is to find out how to develop Smart Apps Creator-based learning media in the Solfegio course at Jakarta State University. This research method uses research and development methods (Research and Development) with the ADDIE approach model through 5 stages Analysis, Design, Development, Implementation, and Evaluation. The research is conducted at Jakarta State University with research subjects namely students in the Solfegio course. Data collecting procedure is made using interview, questionnaires and literature review. The data analysis technique was carried out by distributing questionnaires and then the results obtained were processed and analyzed qualitatively. Checking the validity of the data is done by means of source triangulation in the form of interviews with experts. The results of this study indicate that the development of Smart Apps Creator-based learning media in the Solfegio course at Jakarta State University is in accordance with the steps that are applied. The Smart Apps Creator-based learning media product for the Solfegio course at Jakarta State University is named SOLFUN, Learning Solfegio Is Fun. Based on the validation results from the validators, this learning media gets very good criteria with an average percentage of 90%.